eLearning course for improving civil registration and vital statistics systems - Samuel Mills; Sheila Jagannathan; Jane Kim Lee; Bahie Mary Rassekh (BMC, 2019)
Abstract The World Bank Group (WBG), in partnership with the Global Civil Registration and Vital Statistics (CRVS) Group, the Korea Ministry of Economy and Finance, and the WBG Open Learning Campus, launched the first comprehensive CRVS eLearning course in May 2017. The development of this course demonstrates the commitment and collaboration of development partners and governments working closely together in building the capacity of national institutions to improve CRVS systems in low- and middle-income countries. As of December 2018, over 2300 learners from 137 countries have enrolled in the course. This paper discusses how the course has been developed, disseminated, and evaluated thus far. It also presents the challenges faced and how the course has improved based on feedback from course participants.